2023
DOI: 10.3390/ijms24021300
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in Mouse MT-ATP6 Gene Induces Respiration Defects and Opposed Effects on the Cell Tumorigenic Phenotype

Abstract: As the last step of the OXPHOS system, mitochondrial ATP synthase (or complex V) is responsible for ATP production by using the generated proton gradient, but also has an impact on other important functions linked to this system. Mutations either in complex V structural subunits, especially in mtDNA-encoded ATP6 gene, or in its assembly factors, are the molecular cause of a wide variety of human diseases, most of them classified as neurodegenerative disorders. The role of ATP synthase alterations in cancer dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Interestingly, MT-ATP6 gene was selected by scELMo as a potential target, which implied that cells under different states might have different speeds for cell death [64] or neurodegeneration [65]. These results suggest the potential benefit of exploring the correlation between cellular function and clinical manifestations of this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, MT-ATP6 gene was selected by scELMo as a potential target, which implied that cells under different states might have different speeds for cell death [64] or neurodegeneration [65]. These results suggest the potential benefit of exploring the correlation between cellular function and clinical manifestations of this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, MT-ATP6 gene was selected by scELMo as a potential target, which implied that cells under different states might have different speeds for cell death [56] or neurodegeneration [57]. These results suggest the potential benefit of exploring the correlation between cellular function and clinical manifestations of this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this figure, we found that scELMo identified six novel genes as potential therapeutic targets for cells under the Ascending only state, two novel genes as potential therapeutic targets for cells under the Ascending to descending state, and three genes as potential therapeutic targets for cells under the Ascending w/ root state. Interestingly, MT-ATP6 gene was selected by scELMo as a potential target, which implied that cells under different states might have different speeds for cell death [51] or neurodegeneration [52]. Such results can inspire researchers to explore the correlation between cellular function and clinical manifestations of this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the CMP3013-treated group showed decreased levels of NGAL and cytochrome C, along with an increase in SOD-1 expression (Figures c,d and S14). Additionally, CMP3013 administration in IRI mice resulted in upregulated expression of NQO-1 and SOD-1 mRNA, which are essential mitochondrial antioxidant enzymes. , It also induced elevated transcription of IL-10, an antioxidant and anti-inflammatory cytokine, and ATP6 mRNA, associated with the function of the mitochondrial electron transport complex channel 5 (Figure e). To confirm the ameliorative effects of CMP3013 on impaired kidneys, we reversed the order of treatment for CMP3013 and IRI.…”
Section: Results and Discussionmentioning
confidence: 99%